Tribological properties of carbon nanotube/polymer composites:A mini-review - Miao, Ye; Chen, Qinghui; Li, Yonggui; Zhuo, Dongxian; Wang, Rui (Frontiers in Materials, 2023)
With the development of modern industry, the requirements for mechanical equipment are increasingly stringent, and increasing attention has been paid to reducing wear or lubrication in the movement of mechanical structural parts. Polymers are widely used in the field of mechanical structural parts due to their high processing performance and comprehensive performance. However, the relatively weak mechanical and tribological properties of polymers limit their further application in mechanical equipment lubrication. Incorporation of fillers is a common method to improve the friction properties of polymers. Among various fillers, carbon nanotubes (CNTs) are considered the ideal fillers to significantly improve the tribological properties of polymers. Therefore, this paper reviews the tribological properties of carbon nanotube modified polymer materials. the tribological wear mechanism of polymers and the influence of friction-reducing fillers on the tribological properties of polymers and the related lubrication mechanism explanation are outlined, and the factors influencing the tribological properties of composites by carbon nanotubes and the related lubrication mechanism explanation are analyzed. The presented review will be beneficial for the production of high-performance polymer nanocomposites.